Slope-intercept form is:
y = mx + c
where
m = slope
c = intercept
So rearranging x - y = 3:
x = 3 + y (add y to both sides of the equals)
x - 3 = y (subtract 3 from both sides)
thus
y = x - 3
What is the slope-intercept form of 7x-3y equals 4
y=mx+b in slope intercept form m=slope b=y-intercept
2
-3
Slope-Intercept Form: y = -2x +1
It is in slope intercept form. The slope is 0 and the y-intercept is -2.
What is the slope-intercept form of 7x-3y equals 4
Slope-Intercept Form: y = -2x +1
y=mx+b in slope intercept form m=slope b=y-intercept
It is: y = 0.5x-1.5 in slope intercept form
2
1
y = -1.2x-3 in slope intercept form
-3
Slope-Intercept Form: y = -2x +1
It is: y = 0.25x-0.875 in slope intercept form
y = 6x+8 is already in slope intercept form